Lymphadenopathy and Diseases of the Spleen - Lanzkowsky, Philip (Lanzkowsky's Manual of Pediatric Hematology and Oncology, 2016)
Lymphadenopathy and splenomegaly are common findings in children. Both benign and malignant processes can produce these findings and it is important to distinguish between the two so that appropriate management can be undertaken.